Quizlet as Teaching Media in Navigating Vocabulary Expansion: Systematic Literature Review - Yunita Ayu Riski; Wahyuni, Sri (Universitas Nusantara PGRI Kediri, 2024)
The purpose of study is to investigate the impact and effectiveness of implementing Quizlet medias towards vocabulary expansion in English Subject. In the classroom context, teaching media have evolved into a dynamic and essential component of modern pedagogy. One of famous media in teaching and learning offers various study modes, such as Learning, Matching, and Testing, ensuring a dynamic and engaging learning experience. Using Quizlet, students can learn more vocabulary to master their language. The method used in this study was Systematic Literature Review. The selection of the inclusion and exclusion criteria was determined. We found 243 studies that selected 24 included studies obtained from three databases, ERIC Connectedpapers, and Perplexity.ai. This study analyzes the characteristics, impact, and effectiveness of Quizlet as a teaching medium for navigating vocabulary expansion. The results of this study show that Quizlet has positive and significant implications for vocabulary expansion. Most studies proved that Quizlet is effective in teaching vocabulary among higher education, high school, and English course students.